Preliminary results of a study on active layer hydrology in the discontinuous zone at Schefferville, Nouveau-Québec - Wright, Richard (Géographie physique et Quaternaire, 1979)
A detailed study of the water balance of a lichen tundra underlain by permafrost was started in September 1976. Data collection at the 9 000 m2 site near Schefferville, Québec includes air and ground temperatures, precipitation, évapotranspiration, and changes in soil moisture storage as well as incoming short-wave and net all-wave radiation. It is shown that the development of the active layer is strongly influenced by the amount and distribution of moisture in the soil at freeze-up. Moisture transfer within the unsaturated zone is shown to be strongly influenced by the temperature field within the active layer during freeze-up. During the thaw season the confinement of infiltrated water by permafrost is not only a major soil moisture reservoir and medium for suprapermafrost ground water flow, but it is also shown to maintain évapotranspiration at or near the equilibrium rate for the tundra as well as causing a significant increase in evaporation from permafrost induced wetlands.